"A Man's Lot": Marriage, Military Service, and the First World War. (1st November 2022) - Davis, Cody
Abstract : The study of personal experiences of British and Australian soldiers during the First World War can be further developed through a discrete analysis of married men's interactions with wartime masculine ideals. This article seeks to provide a preliminary insight into such interactions through the case‐study of two officers serving on the Western Front in 1916 and the correspondence they wrote to their wives throughout their military service. British Lieutenant Max Shaw and Australian Lieutenant Cecil Mills both voluntarily enlisted and served in France in 1916. Once they departed their homes to commence training, they immediately began corresponding with their wives, which can be seen as attempts to mediate a clashing sense of domestic and military loyalties. As these men transitioned from a civilian to a military lifestyle, their lingering domestic identities and the importance of their marriage within their sense of manhood continued to influence their adoption of a military identity.